Administrative Performance Reality Educational Supervisors From Physical Educators’ Point of View - Noori, Nadia; Abdul Kareem, Emad (Journal of Physical Education, 2020)
The research aim at identifying administrative performance reality of educational supervisors from physical educators’ point of view. The researchers used the descriptive method on (1845) physical educators from general education directorates in Baghdad (1st Resafa, 2nd Resafa, 3rd Resafa, 1st Khurk, 2nd Khurk, 3rd Khurk) yet only (75) educators were selected from each directorate. The data was collected and treated using proper statistical operations to conclude differences in criteria levels of the two administrative performance scales, educational supervisors were characterized by administrative performance. Finally the researchers recommended the necessity of providing all means for educational supervisors as well as making similar studies on other subjects.